The effectiveness of the KWL strategy in improving the eighth-grade students’ reading ability in recount texts - Maharani Yustari Putri, Prilia; Addeq, Mona (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2025)
This research aimed to investigate whether the KWL (Know, Want to Know, and Learned) strategy was effective in improving the eighth-grade students’ reading ability in recount texts. This study used a quasi-experimental research design. The population in this study consisted of all eighth graders at one of the junior high schools in Malang, whereas the sample consisted of two classes chosen. The control group consisted of 32 students, while the experimental group consisted of 34 students. The data were collected using a pretest and a post-test and analyzed using SPSS software. The results of the test showed that the post-test mean of the experimental group was higher than that of the control group. Moreover, the data were homogeneous and normal, so they can be tested using a t-test. An independent sample test was then used to find the significant difference in post-test scores between the experimental and control groups. The result of the t-test was 0.039, which was smaller than the alpha (α) score, < 0.05. It meant that H0 was rejected and H1 was accepted. In conclusion, the KWL strategy was effective in improving the students’ reading ability in recounting text for the eighth-grade students.